2008
DOI: 10.4049/jimmunol.181.6.3761
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Inhibits Essential Functions of Polymorphonuclear Leukocytes

Abstract: The serum levels of resistin, a 12-kDa protein primarily expressed in inflammatory cells in humans, are increased in patients with chronic kidney disease and in those with diabetes mellitus. Both groups of patients have an increased risk of infections mainly as a result of disturbed polymorphonuclear leukocyte (PMNL) functions. Therefore, we investigated the influence of resistin on human PMNLs. Serum resistin concentrations were determined with a sandwich enzyme immunoassay. Using PMNLs from healthy subjects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 59 publications
5
72
1
Order By: Relevance
“…As previously mentioned, resistin has been ascribed numerous proinflammatory properties in humans, whereas its role in glucose metabolism and homeostasis remains controversial. Furthermore, two recent reports described immunosuppressive effects of resistin on immune cells, including interference with chemotactic and oxidative responses of neutrophils (29), as well as suppression of Ag uptake and presentation by dendritic cells (30). Yet another level of complexity is added by the fact that resistin has a tendency to form oligomers both in vitro and in vivo (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, resistin has been ascribed numerous proinflammatory properties in humans, whereas its role in glucose metabolism and homeostasis remains controversial. Furthermore, two recent reports described immunosuppressive effects of resistin on immune cells, including interference with chemotactic and oxidative responses of neutrophils (29), as well as suppression of Ag uptake and presentation by dendritic cells (30). Yet another level of complexity is added by the fact that resistin has a tendency to form oligomers both in vitro and in vivo (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed the anti-oxidant effect of resistin on neutrophils through PI3K signaling pathway [10]. We hence went on to examine whether resistin can directly inhibit the ROS production by macrophages.…”
Section: Resistin Suppressed Ros Production Which Is Critical For Conmentioning
confidence: 99%
“…Serum resistin level hence has been used as an inflammatory biomarker in various diseases including sepsis, rheumatoid arthritis, and atherosclerosis [7e9]. Furthermore, resistin was recently reported to impair the chemotaxis and production of reactive oxygen species (ROS) in neutrophils [10].…”
Section: Introductionmentioning
confidence: 99%
“…Resistin was also correlated with TNF-α, suggesting that it have a role in the sub-clinical inflammatory state of chronic kidney disease [54]. Resistin may also interfere with the chemotactic ability and oxidative burst of polymorphonuclear 18 leukocytes and might contribute to the disturbed immune response in conditions with increased serum resistin levels, such as uremia [129].…”
Section: Resistin and Chronic Kidney Diseasementioning
confidence: 99%